Autorzy:Maciej Antek, Krzysztof Belka, Piotr Grabowski
Wydawnictwo:Nowa Era
Rok wydania:2015
Oblicz 4.29 gwiazdek na podstawie 7 opinii

`([(1 1/3)^-2-10/2^4]:(-2)^-5)/([(3 1/3)^-1*3^0-1,25^-1*(3/2)^2]^-1)=([(4/3)^-2-10/16]:1/(-2)^5)/([(10/3)^-1*1-(1 1/4)^-1*9/4]^-1)=` 

`=([(3/4)^2-10/16]:1/(-32))/([3/10-(5/4)^-1*9/4]^-1)=([9/16-10/16]*(-32/1))/([3/10-strike4^1/5*9/strike4^1]^-1)=`  

`=(-1/16*(-32/1))/([3/10-9/5]^-1)=(32/16)/([3/10-18/10]^-1)=` 

`=2/(-15/10)^-1=2/(-10/15)=2:(-10/15)=` 

`=2*(-15/10)=2*(-3/2)=-3`